Hypoglycaemic episodes increase the risk of ventricular arrhythmia and sudden cardiac arrest in patients with type 2 diabetes—A nationwide cohort study. Issue 2 (31st October 2019) - Hsieh, Yu‐Cheng; Liao, Ying‐Chieh; Li, Cheng‐Hung; Lin, Jiunn‐Cherng; Weng, Chi‐Jen; Lin, Che‐Chen; Lo, Chu‐Pin; Huang, Kuo‐Ching; Huang, Jin‐Long; Lin, Ching‐Heng; Wang, Jun‐Sing; Wu, Tsu‐Juey; et al.
Abstract: Background: The impact of hypoglycaemic episode (HE) on the risk of ventricular arrhythmia (VA) and sudden cardiac arrest (SCA) remains unclear. We hypothesized that HE increases the risk of both VA and SCA and that glucose‐lowering agents causing HE also increase the risk of VA/SCA in patients with type 2 diabetes (T2D). Methods: Patients aged 20 years or older with newly diagnosed T2D were identified using the Taiwan National Health Insurance Database. HE was defined as the presentation of hypoglycaemic coma or specified/unspecified hypoglycaemia. The control group consisted of T2D patients without HE. The primary outcome was the occurrence of VA (including ventricular tachycardia and fibrillation) and SCA during the defined follow‐up periods. A multivariate Cox hazards regression model was used to evaluate the hazard ratio (HR) for VA or SCA. Results: A total of 54 303 patients were screened, with 1037 patients with HE assigned to the HE group and 4148 frequency‐matched patients without HE constituting the control group. During a mean follow‐up period of 3.3 ± 2.5 years, 29 VA/SCA events occurred. Compared with the control group, HE group had a higher incidence of VA/SCA (adjusted HR: 2.42, P = .04). Patients who had used insulin for glycaemic control showed an increased risk of VA/SCA compared with patients who did not receive insulin (adjusted HR: 3.05, P = .01). Conclusions: The HEs in patients with T2D increased the risk of VA/SCA, compared with those who did not experience HEs. Use of insulin also independently increased the risk of VA/SCA.